Peningkatan Pemahaman Konsep Matematika dan IPA melalui Penggunaan Alat Peraga Bagi Guru SMP di Kabupaten Maros Provinsi Sulawasi Selatan - Rasjid, Yusniar; Andi Syukriani; Nova Dwi Pratiwi Sulastri; Andi Dewi Rizka Ainulia; Israwati Akib (Universitas Sulawesi Barat, 2022)
If students can present concepts in the multiple representations form (verbals, symbols, pictures and concrete objects) and know the structural, students are said to have understood the concept. Props are media that contain concepts in it. Maximizing the use of prop can be related to the characteristics possessed by students. There are different characteristics in students during the process of processing information to generate ideas, especially characteristics in the form of gender (male and female) and cognitive style (Field Independent (FI) and Field Dependent (FD)). The results of the integration of the use of props and the characteristics contained in students to produce a series of activities to maximize the use of props in learning are: (1) Adjusting and understanding the concepts in the props in two other forms (multi-representation), for example with verbal forms and symbols. or in the form of pictures and symbols; (2) Get used to girls to re-explain or justify the three forms of representation of the concept; (3) Ensuring girls can draw pictures of concepts being constructed; (4) Ensure that boys are aware of and reflect on their knowledge and experiences; (5) Ensure that male students get an image of the concept that is being constructed. The results of this training were responded well by the participants and increased the interest and motivation of teachers in creating simple teaching props and using them optimally.